Star wars han solo and chewbacca volume 1 - the crystal run part one ebook - Guggenheim, Marc (Star Wars: Han Solo & Chewbacca,, 2023)
Collects Star Wars: Han Solo & Chewbacca #1-5 And Star Wars: Life Day. The galaxy's best buddies star in a hair-raising adventure from the days before they joined the Rebellion! Loveable rogue Han Solo and his Wookiee partner-in-smuggling, Chewbacca, set off on a heist for none other than Jabba the Hutt - and this time, the Rodian bounty hunter named Greedo is working alongside them! It's supposed to be a nice, straightforward job. What could possibly go wrong? Well, for starters, how about a reunion with the very last person Han expected to see? And when the target safe is cracked, you won't believe what's inside! Plus: Celebrate the galaxy's favorite holiday with a collection of festive tales from all across the saga of Star Wars. Happy Life Day!